Emergence of resistance to linezolid in methicillin resistant Staphylococcus haemolyticus reported from the sub Himalayan region of India - Chauhan, Divya; Verma, Santwana; Verma, Ravi; Sharma, Garima (International Journal of Research in Medical Sciences, 2017)
The spread of resistance among coagulase negative Staphylococci against major drugs is alarming as it limits the treatment options for serious infections. Resistance to linezolid in these organisms is emerging and further compounded by being observed in multidrug resistant strains. It is the only antibiotic available as an oral formulation for resistant Staphylococcal infections and due to the presence of a novel structure and unique mechanism of action, it does not display cross resistance with other classes of antimicrobial agents. However, the widespread use of Linezolid has gradually turned the impending fear of emergence of resistance against this novel drug into a reality. Herein we report a case of sepsis due to methicillin resistant Staphylococcus haemolyticus in a 16-year-old male child found resistant to linezolid, rarely reported from Sub Himalayan region of Indian sub-continent.